If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 + 15x = 33 + -15 Combine like terms: 33 + -15 = 18 -27 + 15x = 18 Solving -27 + 15x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 15x = 18 + 27 Combine like terms: -27 + 27 = 0 0 + 15x = 18 + 27 15x = 18 + 27 Combine like terms: 18 + 27 = 45 15x = 45 Divide each side by '15'. x = 3 Simplifying x = 3
| x+(3x-22)=180 | | A=4tg(2x+1)+3tg(3x-1) | | 11x+49=0 | | ln(3)=8 | | 2+3(t+4)=11 | | 5y-28=6x | | 4x+5=-8x-7 | | .04x+8=24 | | 2(18-6y)-3y=-24 | | 9=3(k-1)+k | | y=cos(2y) | | 2l=21 | | 7x-112=0 | | 21=6n | | 5X+(3X-20)=500 | | b-2b=15 | | 3x-105=0 | | f(y)=cos(2y) | | -3x+6(5x-2)=-6 | | hot+girl= | | 8(x-2)=5x+11+3x | | 3x+3(x+15)=15 | | 4n=0.56 | | x^2y-9y+3x-27=0 | | 5(x+-4)+2x=14 | | y=4(1.666666667)+6 | | 5x-15=20-2x | | 10cos(x)+sin^2(x)=0 | | mx+nc=y | | 2x^4-8=0 | | 2x^5-8=0 | | (-25)x(-13)= |